Expanding the spectrum of phenotypes associated with germline PIGA mutations: A child with developmental delay, accelerated linear growth, facial dysmorphisms, elevated alkaline phosphatase, and progressive CNS abnormalities. Issue 1 (20th November 2013) - van der Crabben, Saskia N.; Harakalova, Magdalena; Brilstra, Eva H.; van Berkestijn, Frédérique M.C.; Hofstede, Floris C.; van Vught, Adrianus J.; Cuppen, Edwin; Kloosterman, Wigard; Ploos van Amstel, Hans Kristian; van Haaften, Gijs; van Haelst, Mieke M.
Abstract Phosphatidyl inositol glycan (PIG) enzyme subclasses are involved in distinct steps of glycosyl phosphatidyl inositol anchor protein biosynthesis. Glycolsyl phosphatidyl inositol‐anchored proteins have heterogeneous functions; they can function as enzymes, adhesion molecules, complement regulators and co‐receptors in signal transduction pathways. Germline mutations in genes encoding different members of the PIG family result in diverse conditions with (severe) developmental delay, (neonatal) seizures, hypotonia, CNS abnormalities, growth abnormalities, and congenital abnormalities as hallmark features. The variability of clinical features resembles the typical diversity of other glycosylation pathway deficiencies such as the congenital disorders of glycosylation. Here, we report the first germline missense mutation in the PIGA gene associated with accelerated linear growth, obesity, central hypotonia, severe refractory epilepsy, cardiac anomalies, mild facial dysmorphic features, mildly elevated alkaline phosphatase levels, and CNS anomalies consisting of progressive cerebral atrophy, insufficient myelinization, and cortical MRI signal abnormalities. X‐exome sequencing in the proband identified a c.278C>T (p.Pro93Leu) mutation in the PIGA gene. The mother and maternal grandmother were unaffected carriers and the mother showed 100% skewing of the X‐chromosome harboring the mutation. These results together with the clinical similarity of the patient reported here and the previously reported patients with a germline nonsense mutation in PIGA support the determination that this mutation caused the phenotype in this family. © 2013 Wiley Periodicals, Inc.